An analysis of teaching strategies designed to improve written communication skills. (2nd January 2019) - Holmes, Amy F.; Zhang, Shage; Harris, Benjamin
ABSTRACT: Accounting instructors can embed effective writing into the curriculum, but how much instruction is enough to make a significant improvement in students' written products? In this quasi-experimental study, we compare the effect of three levels of minimal instructional intervention: all students in the study received a rubric outlining the evaluation criteria and graded feedback on the use of effective business writing (low instruction level); for the medium instruction level, students also received handouts on effective written communication; the high instruction level students received classroom instruction in addition to the handouts, rubric, and feedback. We find that all students show significant improvement in written communication skills in the areas of organization, development, and expression. Students who received the high instruction level show the most improvement. Providing students with the scoring rubric and grading for effective business writing is beneficial to student self-awareness and encourages students to significantly improve their written products.